Correlations Between Acoustic Features, Personality Traits and Perception of Soundscapes - Lindborg, PerMagnus (2017)
The present study reports results from an experiment that is part of Soundscape Emotion Responses (SSER) study. We investigated the interaction between psychological and acoustic features in the perception of soundscapes. Participant features were estimated with the Ten-Item Personality Index (Gosling et al. 2003) and the Profile of Mood State for Adults (Terry et al. 1999, 2005), and acoustic features with computational tools such as MIRtoolbox (Lartillot 2011). We made ambisonic recordings of Singaporean everyday sonic environments and selected 12 excerpts of 90 seconds duration each, in 4 categories: city parks, rural parks, eateries and shops/markets. 43 participants rated soundscapes according to the Swedish Soundscape Quality Protocol (Axelsson et al. 2011) which uses 8 dimensions related to quality perception. Participants also grouped ‘blobs’ representing the stimuli according to a spatial metaphor and associated a colour to each. A principal component analysis determined a set of acoustic features that span a 2-dimensional plane related to latent higher-level features that are relevant to soundscape perception. We tentatively named these dimensions Mass and Variability Focus; the first depends on loudness and spectral shape, the second on amplitude variability across temporal domains. A series of repeated-measures ANOVA showed that there is are patterns of significant correlations between perception ratings and the derived acoustic features in interaction with personality measures. Several of the interactions were linked to the personality trait Openness, and to aural-visual orientation. Implications for future research are discussed.